The growth-employment-poverty nexus in Latin America in the 2000s: Honduras country study - Guillermo Cruces; Gary Fields; David Jaume; Mariana Viollaz (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2015)
During the 2000s Honduras grew less than the average Latin American country and labour market indicators moved, in general, in a worsening direction. The only exceptions were the reduction in the unemployment rate and the improvements in the mix of employment by occupational group and educational level. The country underwent a recession as a consequence of the international crisis of 2008, from which it had not fully recovered by 2012. Most labour market indicators were affected negatively by the crisis, and the majority of them had not recovered their pre-crisis levels by 2012. Poverty has been rising steadily since 2008.
Keywords: O15; J01; J30; 330; Honduras; Latin America; inclusive growth; labour market; poverty